Culture-based and culture-independent approach for the study of the methanogens and obligate anaerobes from different landfill sites - Prakash, Om; Dewala, Sahab Ram; Nimonkar, Yogesh; Patil, Shalaka K.; Chauhan, Ashvini; Yadav, Amit; Dhotre, Dheeraj P.; Ranade, Dilip R. (Frontiers in Microbiology, 2024)
The landfill is a cheap way of solid waste management in developing countries. Majority of landfills are non-sanitary and work as open garbage dumping sites and pose threats to public and environmental health. Therefore, an in-depth understanding of the chemistry and microbiology of landfill is imperative to develop the right policies for landfill management. In the current study, we investigated the chemistry and microbiology of three Indian landfill sites using culture-based and culture-independent molecular approaches. Our data indicate that the nature of landfill varies from site to site in terms of chemistry, pollutants and pathogens. We also enriched and cultivated three methanogens using an optimized medium and constructed two high-quality draft genomes from enriched microbiomes using metagenome-assembled genomes approaches. The Phylogenomic study of one draft genome showed the highest 93% sequence similarity with members of Methanomassiliicoccaceae and always enriched with Acholoplasma and Anaerohalosphaera lusitana. Despite all the efforts, we did not isolate it in pure culture and hypothesized that for the cultivation of some not-yet-cultured methanogen, presence of other organisms plays an important role, and their syntrophic interaction must be discerned for its successful cultivation in future. Cocultivation of amino acid degrading organisms indicate that their co-culture can assist to boost the growth methanogens. In addition, our data indicated that landfill leachate contains a heavy load of pollutants and treatment is must before discharge in nature or use in irrigation or biofertilizer.